2014
DOI: 10.1186/1742-4933-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and subclinical airway inflammation in the SALIA cohort study

Abstract: BackgroundThe association between long-term exposure to air pollution and local inflammation in the lung has rarely been investigated in the general population of elderly subjects before. We investigated this association in a population-based cohort of elderly women from Germany.MethodsIn a follow-up examination of the SALIA cohort study in 2008/2009, 402 women aged 68 to 79 years from the Ruhr Area and Borken (Germany) were clinically examined. Inflammatory markers were determined in exhaled breath condensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Increased frailty of the epithelial barrier, inflammation, oxidative stress, and interaction with genetic and epigenetic determinants have been proposed. Research in adults, including subjects from the cohorts included in our analysis, has suggested a role of air pollution in local inflammation measured in exhaled breath condensate and induced sputum (using ESCAPE exposure estimates) ( Vossoughi et al 2014 ), interaction with oxidative stress genes ( Castro-Giner et al 2009 ), or novel DNA methylation markers ( Sofer et al 2013 ). Ambitious programs with comprehensive environmental exposure assessment and biological markers are starting in childhood populations ( Vrijheid et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased frailty of the epithelial barrier, inflammation, oxidative stress, and interaction with genetic and epigenetic determinants have been proposed. Research in adults, including subjects from the cohorts included in our analysis, has suggested a role of air pollution in local inflammation measured in exhaled breath condensate and induced sputum (using ESCAPE exposure estimates) ( Vossoughi et al 2014 ), interaction with oxidative stress genes ( Castro-Giner et al 2009 ), or novel DNA methylation markers ( Sofer et al 2013 ). Ambitious programs with comprehensive environmental exposure assessment and biological markers are starting in childhood populations ( Vrijheid et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…We chose to focus our analysis on the four inflammatory genes included in these genes, including two inflammatory cytokines ( IFN- γ and IL-6 ), intercellular adhesion molecule 1 ( ICAM-1 ), and Toll-like receptor 2 ( TLR-2 ). The choice of these four inflammatory genes was aligned with previous literature on PM and inflammation, as well as subclinical inflammation and the risk of T2DM (Bind et al 2012; Blüher et al 2002; Herder et al 2013; Madrigano et al 2010; van Eeden et al 2001; Vossoughi et al 2014). Specifically, IFN- γ and IL-6 encode for inflammatory cytokines that facilitate cell-to-cell communications in the inflammatory cascade, ICAM-1 encodes for a glycoprotein that is often expressed on the cell surface of endothelial cells and leukocytes, ICAM-1 glycoproteins are important for cell surface adhesion, transmigration and homing of leukocytes from the circulation to the target tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies on air pollution and asthma have concentrated on children, but whether different mechanisms are involved in patients with adult-onset asthma who often are less atopic remains unclear. In elderly women, long-term exposure to traffic- and industrial-related air pollution was associated with increased inflammatory markers (leukotriene B 4 and TNF- α ) in exhaled breath condensate and induced sputum [ 236 ]. Oxidative stress has been hypothesized as the mechanism of how air pollution might cause asthma.…”
Section: Risk Factors For Adult-onset Asthmamentioning
confidence: 99%